Figures 4-10 from Lu Donghui, et al. - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2014)
Figures 4-10 from Lu D H, Tabil L G, Wang D C, Wang G H, Wang Z Q. Optimization of binder addition and compression load for pelletization of wheat straw using response surface methodology. Int J Agric & Biol Eng, 2014; 7(6): 67－78.